2010
DOI: 10.4269/ajtmh.2010.09-0676
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis in Travelers from Non-Endemic Countries, 1973–2008

Abstract: Japanese encephalitis (JE) is a severe disease and a risk for travelers who visit JE-endemic countries. We reviewed all published JE cases in travelers from non-endemic areas from 1973 through 2008, and assessed factors related to risk of infection. There were 55 cases that occurred in citizens of 17 countries. Age range of case-patients was 1–91 years (median = 34 years). Ten (18%) persons died and 24 (44%) had mild to severe sequelae. In a detailed risk assessment of 37 case-patients, 24 (65%) had spent ≥ 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(77 citation statements)
references
References 43 publications
0
65
0
5
Order By: Relevance
“…The occurrence of symptomatic to asymptomatic infection ratio is 1: 25-1000 (1:300 on an average) (Saxena & Dhole, 2008). The incubation period ranges between 5 and 15 days, and symptoms are pyrexia, chillness, lethargy, muscle ache, headache, abdominal pain and vomition (Hills et al, 2010).…”
Section: Clinical Features In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of symptomatic to asymptomatic infection ratio is 1: 25-1000 (1:300 on an average) (Saxena & Dhole, 2008). The incubation period ranges between 5 and 15 days, and symptoms are pyrexia, chillness, lethargy, muscle ache, headache, abdominal pain and vomition (Hills et al, 2010).…”
Section: Clinical Features In Humansmentioning
confidence: 99%
“…Vaccination of people living in endemic areas, lab personnel with a possible for JEV exposure, travellers staying for more than one month in the prevalent zone and also to travellers staying less than a month during the JE transmission season is the reliable strategy for the prevention of JE (Fischer et al, 2010). At present, inactivated mouse brain-derived (Nakayama and Beijing-1) and Vero cell-based inactivated (Beijing-1, P-3, SA 14-14-2, Kolar strain-JEV 821564XY) vaccines are available.…”
Section: Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…54 In a recent review of JE cases in travelers, a detailed risk assessment of 37 cases revealed that 35% had spent less than 1 month in JE-endemic areas and thus would not have been recommended vaccination. 55 Nonetheless IXIARO Ò provides proven protection with a favorable safety profile and outdated guidelines and recommendations should be revised according to an expert recommendation: travelers to rural areas of Asia should generally be recommended vaccination. 56 For travelers, a primary immunization regimen of 28 d can take too long to complete before departure.…”
Section: Public-healthmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention, USA, JE occurs in less than one case per million travelers to Asia 26 and from 1973 to 2001, only 58 cases of JE have been reported among travelers from non-endemic countries. 27 Risk is likely to be higher if the period of stay in the endemic region is longer and if involved in outdoor activities in rural areas. 28,29 Assuming an annual incidence of ten per 1,000 in the region being visited, the risk of developing the disease during a month long visit during the transmission season came to one per 5,000.…”
Section: History Distribution and Occurrencementioning
confidence: 99%